Random regression models using Legendre polynomials or linear splines for test-day milk yield of dairy Gyr (Bos indicus) cattle - Pereira, R. J. [UNESP]; Bignardi, A. B. [UNESP]; El Faro, L.; Verneque, R. S.; Vercesi Filho, A. E.; Albuquerque, L. G. [UNESP] (American Dairy Science Association, 2013)
Studies investigating the use of random regression models for genetic evaluation of milk production in Zebu cattle are scarce. In this study, 59,744 test-day milk yield records from 7,810 first lactations of purebred dairy Gyr (Bos indicus) and crossbred (dairy Gyr × Holstein) cows were used to compare random regression models in which additive genetic and permanent environmental effects were modeled using orthogonal Legendre polynomials or linear spline functions. Residual variances were modeled considering 1, 5, or 10 classes of days in milk. Five classes fitted the changes in residual variances over the lactation adequately and were used for model comparison. The model that fitted linear spline functions with 6 knots provided the lowest sum of residual variances across lactation. On the other hand, according to the deviance information criterion (DIC) and Bayesian information criterion (BIC), a model using third-order and fourth-order Legendre polynomials for additive genetic and permanent environmental effects, respectively, provided the best fit. However, the high rank correlation (0.998) between this model and that applying third-order Legendre polynomials for additive genetic and permanent environmental effects, indicates that, in practice, the same bulls would be selected by both models. The last model, which is less parameterized, is a parsimonious option for fitting dairy Gyr breed test-day milk yield records. © 2013 American Dairy Science Association.
Keywords: Covariance function; Orthogonal polynomial; Random regression model; Spline; animal; Bayes theorem; biological model; breeding; cattle; female; genetics; lactation; physiology; quantitative trait; statistical model; Animals; Bayes Theorem; Breeding; Cattle; Female; Lactation; Linear Models; Models, Genetic; Models, Statistical; Quantitative Trait, Heritable; Bos; Bos indicus